UNDERSTANDING TEACHER AND STUDENT PERCEPTIONS OF GAMIFIED LEARNING AND ITS IMPACT ON LEARNING MOTIVATION THROUGH THE WAYGROUND PLATFORM - Fithriyah Shofiana Pratiwi; Imron Fauzi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine teacher and student perceptions of gamified learning and its influence on learning motivation in Islamic elementary school settings. The research employs a qualitative multiple-case study approach supported by descriptive quantitative data to explore how gamification is interpreted, experienced, and accepted by teachers and students. Data were collected through questionnaires, in-depth interviews, focus group discussions, classroom observations, and documentation. Thematic analysis based on the interactive model of Matthew B. Miles and A. Michael Huberman was used to identify key categories of perception and motivational change, while questionnaire data were analyzed descriptively to measure shifts in motivation levels. The findings reveal that teachers perceive gamified learning as a practical and engaging approach that facilitates instructional activities, enhances classroom interaction, and promotes active participation. Students report increased enjoyment, challenge, and curiosity, contributing to stronger intrinsic motivation as conceptualized in Self-Determination Theory. Quantitative results indicate a noticeable improvement in motivation scores following the implementation of gamified activities, supported by observable increases in student engagement. Nevertheless, several challenges were identified, including limited digital literacy among teachers and occasional technical constraints. Overall, this study underscores the significance of integrating gamification into Islamic elementary education and offers empirical insights into digital pedagogy, instructional media selection, and teacher readiness for technology-enhanced learning.